Mineral concentration in forage and bovine exposed to the eruption of Lonquimay volcano - Wittwer, Fernando; Araya, Oscar; Ceballos, Alejandro; Böhmwald, Helga (Pesquisa Agropecuaria Brasileira, 1997)
Lonquimay volcano (LV) is located in the southern Andes of Chile; it began erupting in December/88, and was active for 13 months. The eruption products can affect the mineral concentration in forages; consequently, animal health can be affected. To analyze the contents of Ca, P, Mg, Na, K, B, Cu, Fe, Mn, Mo, and Zn in pastures from the Lonquimay valley, samples of forage were taken from 5 farms near to LV during two years after cessation of the eruption. Also the concentration of Ca, P, Mg, and Cu in serum of grazing cows was analyzed. The mineral concentration in the pastures and in the serum were described by means (x) and by standard deviation (SD); the frequency of samples with mineral contents below or above requirements for grazing cattle was plotted. No tendency to increase or decrease the serum concentration of minerals in grazing cattle was observed; moreover, no abnormal concentrations of Ca, P, and Mg were found, but Cu in serum was low. The contents of Ca, Mg, K, B, Fe, Mn, and Mo in the pastures were enough to fill the mineral requirements for grazing cattle; but Cu, Na, and Zn were not. The low concentration of Cu in the serum was due to the low contents of the mineral in the pasture.